EDUCATION FOR WOMEN: a Thematic Hadith Study with a Grounded Theory Approach - Mila, Mila; Firdaus, Amar; Rosyadi, Salim; Millah, Mus'idul; Alif, Muhammad (Al-Bukhari : Jurnal Ilmu Hadis, 2024)
Some people consider that women do not need to study higher, because women only take care of household affairs. Higher education is considered an obstacle to life goals. This research aims to discuss education for women based on hadith. This research uses a type of qualitative research, namely with a thematic method of hadith with a grounded theory approach. The formal object of this research is the understanding and urgency of education for women which is grouped based on hadith themes. Meanwhile, the material object in this study is the argument that women do not need to study. The discussion in this study explains that women are free to do something, especially in learning. This study concludes that through the grounded theory approach, the themes of women's education hadith are obtained. Education for women is mandatory and prioritized, women also have the right to education. Because it is from women that a new generation will be created and that new generation must be educated to create a quality generation.